2012
DOI: 10.3386/w18574
|View full text |Cite
|
Sign up to set email alerts
|

Free to Choose? Reform and Demand Response in the English National Health Service

Abstract: The impacts of choice in public services are controversial. We exploit a reform in the English National Health Service to assess the impact of relaxing constraints on patient choice. We estimate a demand model to evaluate whether increased choice increased demand elasticity faced by hospitals with regard to clinical quality and waiting time for an important surgical procedure. We find substantial impacts of the removal of restrictions. Patients became more responsive to clinical quality. Sicker patients and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 51 publications
5
56
0
4
Order By: Relevance
“…Additionally, the article is instructive for recent debates in economics about salience, and the propensity of market actors to pay disproportionately more attention to information presented in some formats than others (Chetty et al, 2009;Falkinger, 2008;Hirshleifer and Teoh, 2003). Our findings also relate to work in industrial organization and the under-researched question of how demand responsiveness to beliefs about quality is moderated by the degree of market competition (Beckert et al, 2012;Gaynor et al, 2012;Porter, 1974). The present study is additionally of interest to decision-makers at both university and departmental levels who have increasingly confronted questions about the pay-offs from investments to improve student satisfaction scores and popular league table rankings (Hazelkorn, 2008;The Economist, 2013).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Additionally, the article is instructive for recent debates in economics about salience, and the propensity of market actors to pay disproportionately more attention to information presented in some formats than others (Chetty et al, 2009;Falkinger, 2008;Hirshleifer and Teoh, 2003). Our findings also relate to work in industrial organization and the under-researched question of how demand responsiveness to beliefs about quality is moderated by the degree of market competition (Beckert et al, 2012;Gaynor et al, 2012;Porter, 1974). The present study is additionally of interest to decision-makers at both university and departmental levels who have increasingly confronted questions about the pay-offs from investments to improve student satisfaction scores and popular league table rankings (Hazelkorn, 2008;The Economist, 2013).…”
Section: Introductionmentioning
confidence: 67%
“…Another novel finding of our study, which builds on recent work in health-care settings (Beckert et al, 2012;Gaynor and Town, 2011;Gaynor et al, 2012), concerns market concentration, competition and power. We show that the impact of information on quality derived from league tables is strongly influenced by the number of providers in a particular subject or geographical area.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Since hospitals are expected to be responsive to patient demands, increasing the importance of distance will lessen the importance of other aspect of the demand function. The current literature on the determinants of patient choices shows that quality of care, the distance to the hospital, waiting times, and other hospital amenities are the main factors taken into account by patients when making this choice (Baker, Bundorf, & Kessler, 2016;Beckert & Kelly, 2017;Gaynor, Propper, & Seiler, 2016;Gravelle, Santos, Siciliani, & Goudie, 2012;Victoor, Delnoij, Friele, & Rademakers, 2012). Thus, the decrease in options available to patients could lessen the providers' incentives to provide high quality care and to limit waiting times.…”
Section: Policy Implications For the Organization Of Carementioning
confidence: 99%
“…Their estimates confirm that reforms giving patients choice of hospital increased patient elasticity of demand with respect to service quality. They found considerable heterogeneity in their estimates, with sicker patients responding more to the reform, but did not find significant response differences by income (Gaynor, Propper, and Seiler 2012). Cooper et al (2010) also examine the effects of increased competition in the NHS using a difference-in-differences approach with "exposure" to competition and time as the two differences.…”
Section: Hospital Competitionmentioning
confidence: 99%
“…Using discharge data and comparing variation in market structure across hospitals through market concentration, they found that hospitals competed on quality, resulting in improvements in mortality and length of stay. In a follow-up paper (Gaynor, Propper, and Seiler 2012), the authors estimate a structural demand model using data from the same reforms for coronary artery bypass graft surgery. Their estimates confirm that reforms giving patients choice of hospital increased patient elasticity of demand with respect to service quality.…”
Section: Hospital Competitionmentioning
confidence: 99%